IDENTIFIKASI MISKONSEPSI IPA MATERI TENTANG SIFAT-SIFAT CAHAYA MENGGUNAKAN CERTAINTY OF RESPONS INDEX (CRI) PADA SISWA KELAS V SD KATOLIK ST. THERESIA ENDE 3 - Theresia Novita Riti; Nining Sar'iyyah; Gregorius Sebo Bito (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study aims to describe the concept of light concept misconceptions through the CRI method in the fifth grade students of SDK St. Theresia Ende 3. This type of research is descriptive qualitative. Data were collected by diagnostic tests, interviews and documentation. The results showed that most of the students had misunderstood the material properties of light. Of the many students who experience misconceptions that occur in the VD class at the St.Theresia Ende 3 SDK, they come from the students themselves, from the teacher conveying the wrong concept, and the teaching method is not appropriate.